Lissencephaly: Causal Heterogeneity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Clinical, cytogenetic and molecular studies in 65 patients with isolated lissencephaly sequence (ILS) are reported from Indiana University School of Medicine, Indianapolis; Tufts New England Medical Center, Boston; Eastern Virginia Medical School, Norfolk; University of Washington School of Medicine, Seattle; and Baylor College of Medicine, Houston.